Pengaruh Kualitas Sumber Daya Manusia terhadap Kinerja Pegawai Badan Pendidikan dan Pelatihan Provinsi Kalimantan Tengah - Masrukin Masrukin; Awina Theresia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This research aims to understand how much influence the quality of human resources on its employees ' performance in the central Kalimantan Province training agency. The method used in this study with a total sampling technique of 25 people consisting of a free variable X (human resource quality) and Y-bound variable (performance). Data is collected through questionnaires and supported by library studies. Data analysis techniques using a Likert scale. Human resources ' Kulitas have significant positive impact on the performance of agency officers in central Kalimantan province. With the quality of human resources that are continuously improved, both in terms of knowledge and skills tailored to the needs of the Organization, the implementation of tasks and functions of each officer can be done optimally and will be Performance as planned. This is based on hypothesized testing that has been done. Simple linear regression equation y = 4,435 + 27, 97x. Where, when the effect of human resources quality on performance in the central Kalimantan Province training Agency was declared zero (0) the performance of the training body amounted to 27.97. The implications that can be recommended in this study are as follows: (1) need to be held for employees as a comparative study, (2) need to be reflected in the organizational structure to allow the placement of the Employees in accordance with their own, (3) need to harmonizes vision and mission, approaches, strategies, and operational activities to create teamwork that can strengthen the institution itself